2020
DOI: 10.18593/race.23702
|View full text |Cite
|
Sign up to set email alerts
|

Preservação da riqueza socioemocional e a profissionalização em empresas familiares

Abstract: Empresas familiares dominam os negócios em grande parte das economias mundiais exercendo influência sobre o ambiente econômico-social. Este estudo objetiva investigar como a riqueza socioemocional impacta no processo de profissionalização em uma empresa familiar. A pesquisa caracteriza-se como exploratório, estudo de caso qualitativo realizado em uma empresa localizada em Santa Catarina com 50 anos de história, sendo uma empresa S.A de capital fechado de grande porte. As entrevistas foram analisadas pela abord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
(47 reference statements)
0
6
0
2
Order By: Relevance
“…With more detail, it is possible to state that comparing family and non-family businesses, the significant differences occur in the items related to changes in the legislations of work ( t = 2.09 and p < 0.05), taxes ( t = 2.56 and p < 0.05) and environment ( t = 3.21, p < 0.01). Family businesses give extremely high importance to high-quality financial information and legal aspects as referred by Borralho et al (2020) and Ames et al (2020). Ames et al (2020) also refer to the importance that family businesses give to internal control, which is useful to verify the compliance with the internal norms of the firm and with the current legislation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With more detail, it is possible to state that comparing family and non-family businesses, the significant differences occur in the items related to changes in the legislations of work ( t = 2.09 and p < 0.05), taxes ( t = 2.56 and p < 0.05) and environment ( t = 3.21, p < 0.01). Family businesses give extremely high importance to high-quality financial information and legal aspects as referred by Borralho et al (2020) and Ames et al (2020). Ames et al (2020) also refer to the importance that family businesses give to internal control, which is useful to verify the compliance with the internal norms of the firm and with the current legislation.…”
Section: Resultsmentioning
confidence: 99%
“…Reputation is a key organizational asset, especially in family businesses, because these tend to establish long-term partnerships with stakeholders. Ames et al (2020) verified that the main factor to introduce professionalization in a family business was survival in a competitive environment. They also observed that the family has an active and directive role in terms of the control and influence on the decisions, both on strategic and tactical levels and outline the importance given to the image of the family's name, social relationships and the desire to maintain the family's business.…”
Section: Succession In Family Businessesmentioning
confidence: 86%
See 1 more Smart Citation
“…A profissionalização em empresas familiares diz respeito ao envolvimento de membros familiares na organização e à opção por gestores, funcionários e colaboradores não familiares (AMES et al, 2020). Segundo os mesmos autores, a profissionalização é um processo de transição que busca a formalização e o auxílio na estruturação da organização, podendo ocorrer pela inserção de pessoas fora da família, mas também pela capacitação de membros familiares.…”
Section: Caracterização Da Empresa E Presença Da Famíliaunclassified
“…Entre os estudos nacionais também foram encontrados dois trabalhos publicados em periódicos com abordagem da preservação da riqueza socioemocional envolvendo a profissionalização (Ames, Nolli, Beck, & Mucci, 2020), e como as questões emocionais influenciaram no processo de declínio da empresa familiar (Buchweitz, Cruz, Barbosa, & Pereira, 2019).…”
Section: Introductionunclassified